1987
DOI: 10.1115/1.3225964
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial Creep-Fatigue Failure Characteristics in Two FCC Materials

Abstract: This paper describes the failure mode observed in two types of FCC structural materials: waspaloy and type 316 stainless steel as a result of biaxial low cycle fatigue at elevated temperatures. Torsional cycling was applied at high as well as low strain ranges. Creep effect was assessed by introducing hold periods of 90 seconds in the waspaloy tests and 30 minutes in the stainless steel tests. Data obtained from fatigue and creep-fatigue tests have shown that the failure process in the two materials was contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…16 with various literature data from uniaxial tests [45,53,[67][68][69] as well as torsional tests [70][71][72]. On the basis of these literature data a fit curve as well as a corresponding scatter band for the factor two were approximated and included in Fig.…”
Section: Fatigue Livesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 with various literature data from uniaxial tests [45,53,[67][68][69] as well as torsional tests [70][71][72]. On the basis of these literature data a fit curve as well as a corresponding scatter band for the factor two were approximated and included in Fig.…”
Section: Fatigue Livesmentioning
confidence: 99%
“…Due to the low cycle fatigue tests with constant frequencies f of 0.05 Hz according to Clavel and Pineau [53] and 0.3 Hz carried out by Cowles et al [45], different strain rates for all strain amplitudes are compared. Zamrik et al [70][71][72] No further details about the testing parameters were given by Clavel and Pineau [53].…”
Section: Fatigue Livesmentioning
confidence: 99%
“…An increase in crack growth rate with temperature was observed in both air and vacuum and was attributed to temperature dependence of the elastic modulus. Zamrik and Zahiri 42 concluded that temperature had a strong effect on the failure modes of the waspaloy material at 649°C -precipitation of carbide particles caused formation of embrittled regions. Huthmann and Gossmann, 43 however, studied fatigue and creep crack growth behavior of the X6CrNil8 steel (type 304 stainless steel) in air and flowing sodium at 823°K and reported no significant influence of the environment.…”
Section: Effects Of Temperature and Environmentmentioning
confidence: 99%